Análisis de la incidencia en la baja recaudación de los impuestos, generada a través de la actividad económica informal, que se encuentra organizada dentro del casco comercial del cantón Quevedo periódo 2012 - Elizondo Saltos, Adolfo Hernán (2012)
Informal trade has increased so rapidly as an alternative employment as obtaining an additional income to help meeting the basic needs of our population. That is why this thesis shows a field research in the central town of Quevedo Canton, which provides information on the current situation of informal trade and the ability of traders to carry it out. As a contribution to this solution has made this research work "ANALYSIS OF THE IMPACT ON THE LOWER tax collections, generated through informal economic activity, that is organized Inboard QUEVEDO CANTON TRADE PERIOD 2011", structured in different chapters containing the following: In the field study we observed that traders use the money on other activity is and do not have adequate accounting control there is also apart that does not pay muchim portance when making their statements. Informal traders pay adaily tribute to the municipality by the occupation of public roads also make their annual returns by paying patent RISE an dhy gieneand a municipal license adding an annual contribution of$ 14,976. The causes for the low taxes in the informal sector to 40% for the economic crisis there, 30% believe that evade taxes, while another 30% said they have not legalized the business.